Pengukuran Kemampuan Keuangan Daerah Dengan Rasio Share dan Growth - Rahman, Zubaidah (Gorontalo Accounting Journal, 2022)
This study aims to measure the regional financial capacity. The data was used in the form of Financial Statements obtained from the Finance Agency of North Gorontalo Regency. The analytical method used is using share and growth analysis tools. The results of the research with share analysis show that North Gorontalo Regency during the five years, 2016-2020, has a meager criterion value, meaning that North Gorontalo Regency does not yet have the financial capacity to finance all of its total expenditures and is still dependent on the Central Government. Furthermore, the study's results as measured by growth analysis showed that North Gorontalo Regency during the 2016-2020 period had a low criterion value. This means that North Gorontalo Regency has poor growth in Regional Original Income (PAD) so North Gorontalo Regency does not yet have optimal prospects for future economic growth.